Adaptation and Implementation of Pictorial Conversation Aids for Early-Stage Breast Cancer Surgery and Reconstruction: A Quality Improvement Study - Durand MA; Bannier M; Aim MA; Mancini J (Patient Preference and Adherence, 2023)
Marie-Anne Durand,1– 3 Marie Bannier,4 Marie-Anastasie Aim,5,6 Julien Mancini7 1CERPOP, Université de Toulouse, Inserm, Université Toulouse III Paul Sabatier, Toulouse, France; 2The Dartmouth Institute for Health Policy & Clinical Practice, Dartmouth College Lebanon, Lebanon, NH, USA; 3Unisanté, Centre universitaire de médecine générale et santé publique, Lausanne, Switzerland; 4Institut Paoli-Calmettes, Marseille, France; 5AP-HM, Délégation à la Recherche Clinique et à l’Innovation, Marseille, France; 6Aix-Marseille Univ, LPS, Aix-en-Provence, France; 7Aix-Marseille Univ, APHM, INSERM, IRD, ISSPAM, SESSTIM, “Cancer, Biomedicine & Society” Group, Equipe Labellisée LIGUE, Hop Timone, Marseille, FranceCorrespondence: Julien Mancini, SESSTIM (Aix-Marseille Univ, Inserm, IRD) “Cancer, Biomedicine & Society” group, Institut Paoli-Calmettes, 232 Bd Ste Marguerite, BP 156, Marseille Cedex 9, Marseille, 13273, France, Tel +33 491 22 35 01, Email julien.mancini@univ-amu.frPurpose: After a diagnosis of early-stage breast cancer, women of lower socioeconomic position (SEP) report worse outcomes than women of higher SEP. A pictorial conversation aid was shown to improve decision outcomes in controlled contexts. No such intervention existed in France. In Phase 1, our aim was to adapt, for use in France, two pictorial conversation aids for breast cancer surgery and reconstruction. In Phase 2, our aim was to implement them in a regional cancer center serving a diverse population.Patients and Methods: In phase 1, we used iterative qualitative methods to adapt the conversation aids with a convenience sample of patients and health professionals. In phase 2, we tested their implementation using PDSA cycles with volunteer surgeons.Results: In phase 1, we interviewed 10 health professionals and 5 patients to reach thematic data saturation. They found the conversation aids usable and very acceptable (especially patients) and suggested small changes to further simplify the layout and content (including a glossary). In phase 2, three surgeons started the first PDSA cycle, for 4 weeks. Only one additional surgeon agreed to take part in the second cycle. The third cycle was cancelled since no new surgeon agreed to take part. Time was a barrier for 2 out of 4 surgeons, potentially explaining the difficulty recruiting for the third cycle. The evaluation was otherwise positive. The surgeons found the conversation aids very useful during their consultations and all intended to continue using them in the future.Conclusion: It was possible to adapt, for use in France, pictorial conversation aids proven to be effective elsewhere. While the adapted conversation aids were deemed usable by health professionals and very acceptable to patients, their implementation using PDSA cycles proved slow.Plain Language Summary: After a diagnosis of early-stage breast cancer, women of lower health literacy and socioeconomic position report worse outcomes than women of higher health literacy and socioeconomic position. Pictorial conversation aids were shown to improve decision outcomes in controlled contexts. No such intervention existed in France. Our aims were to adapt, for use in France, two lower health literacy pictorial conversation aids for breast cancer surgery and reconstruction, and then to implement them in a regional cancer center. Health professionals and patients found the conversation aids usable and very acceptable (especially patients) and suggested changes. Regarding implementation, the evaluation was also positive but time was a barrier for surgeons, and it was difficult to recruit many volunteers to use such conversation aids during their consultations.Keywords: shared decision-making, decision support techniques, breast cancer disparities, lower socioeconomic position